Nano-indentation study of dislocation evolution in GaN-based laser diodes - Jingjing Chen; Xujun Su; Guobing Wang; Mutong Niu; Xinran Li; Ke Xu (Discover Nano, 2024)
Abstract The slip systems and motion behavior of dislocations induced by nano-indentation technique in GaN-based LDs were investigated. Dislocations with burgers vector of b = 1/3 <11 $$\overline{2}$$ 2 ¯ 3> were introduced on either {11 $$\overline{2}$$ 2 ¯ 2} <11 $$\overline{2}$$ 2 ¯ 3>, or {1 $$\overline{1}$$ 1 ¯ 01} <11 $$\overline{2}$$ 2 ¯ 3> pyramidal slip systems in the upper p-GaN layer. Besides, {0001} <11 $$\overline{2}$$ 2 ¯ 0> basal slip system was also activated. The AlGaN/InGaN multi-layers in device can provide mismatch stresses to prevent dislocations from slipping through. It was observed that the density of dislocations induced by the indenter significantly decreased from the upper to the lower regions of the multi-layers. The a + c dislocations on pyramidal slip planes were mostly blocked by the strained layers.